PEMAHAMAN MASYARAKAT DALAM SOSIALISASI PENCEGAHAN STUNTING PADA BALITA - Sundoro, Totok; Firmansyah, Ramadhani; Puspitasari, Eri (HIKMAYO: JURNAL PENGABDIAN MASYARAKAT AMAYO, 2024)
The term stunting is defined as a condition of failure to grow so that a child's height is shorter than the height of his age, which is caused by a long-term lack of nutritional intake during the first 1000 days of life. This condition has the impact that adults are vulnerable to attacks from non-communicable diseases such as heart disease, stroke, diabetes or kidney failure. Most people do not understand about stunting and still think that stunting or dwarfism, as it is commonly used in society, occurs due to hereditary factors. This community service is carried out for knowledge, changing behavior, positive attitudes regarding efforts to prevent stunting in toddlers in RT 009 Dusun Bintaran, Jambidan Village, Banguntapan District, Bantul. The methods used include screening for toddlers and health promotion as well as assessing the level of community understanding before and after being given health promotion regarding prevention and control for toddlers. The results of the toddler nutrition screening, of 13 toddlers, there were 12 (92%) toddlers with good nutrition, while the results of the pre-test and post-test which were attended by 18 respondents can be stated that the pre-test results regarding the level of knowledge of respondents regarding the stunting prevention program were 12 respondents (67 %) understand about stunting prevention programs while based on the post test results there are 18 respondents (100%) who understand about stunting prevention programs. Health promotion activities through outreach about preventing and treating stunting in toddlers need to be carried out continuously so that the public better understands how to prevent, change behavior, positive attitudes and eliminate the incidence of stunting in toddlers.